(untitled) (Journal of Oriental Studies, 2016)
Everybody knows that sources which give us true information about history of Central Asia, including Kazakhstan are Chinese, Persian and Arabic captions. They were found in the result of travels of geographers who were eyewitnesses all of these events. There were also historians who collected all the information from previous sources and from tellers of eyewitnesses. This article is dedicated to variation of translation of Kazkhstan`s toponyms which are seen in work of Ibn al-Asir «al-Kamil fit-tarih».